What Is Natural Theology? (and Should We Dispense with It?) - Harrison, Peter 1955- (2022)
In a series of impressive works, Alister McGrath has made a major contribution to contemporary natural theology. The natural theology he has in mind is not the “established” variety, which seeks to provide rational support for religious beliefs from nonreligious premises. Rather, it is an explicitly Christian natural theology that involves “seeing” the world through the lens of Christian revelation. Nevertheless, McGrath seems to hold that a sufficiently capacious understanding of natural theology can encompass both the established version and the broader vision that constitutes his own project. This article suggests that there is a significant tension between these two conceptions of natural theology. It argues that the supposedly “established” version of natural theology was never really established within the Christian tradition to any significant degree, but was instead belatedly projected onto it for various reasons. The historical tradition comports with McGrath's project, but not with his generous comprehension of the established conception within a genuinely Christian natural theology.
Keywords: theology of nature; physicotheology; Philosophy of religion; Nature; Naturalism; Natural Theology; Alister McGrath; Design Argument